KINERJA PERUSAHAAN dan AUDIT MANAJEMEN KEUANGAN - Asti Nurul Suci; Karsiati Karsiati (FEB UNTAG Semarang, 2019)
This study aims to study the application of financial management audits at PT. Mowilex Indonesia Regional Indo Central. The focus of this research is the audit of financial management organizations and operational policy audits. This research uses qualitative research methods using case studies. Informants in this study published Branch Manager, SPV Finance & Accounting, SPV Warehouse, and Sales Admin. The analytical tool used in this study is the analysis of the Miles and Huberman model and triangulation.The results showed that financial management audits have not been conducted in a fixed period or period. In the application of financial management audits, much remains to be considered, among others: there are no specific members of the audit team, and the implementation of financial management audits regulates the schedule of each member. The duties, authorities and responsibilities of the financial department have not yet been established. Unwritten financial policies and regulations. There has not been any handling of inventory of goods whose sales are slow. Poor record keeping on the warehouse stock card and collection of goods that are not in accordance with the travel permit, resulting in a difference in the number and number of batches between the system and its physical at the time of the stock taking. Solutions to overcome the challenges that occur in the implementation of financial management audits include: recruiting new Human Resources equivalent to Bachelor degree to become an auditor and making Standard Operating Procedures (SOP) related to the audit implementation schedule. Develop standard job descriptions that are compiled and explained as well as compiling work procedures established by the head office and applied to all branch offices. Make policies related to managing petty cash and credit sales receivables. Manage faster sales completion: provide special discounts or sell at low prices, make samples for projects, repair and return headquarters or transfer to other branches that need the goods, and recycle these items and then use them for CSR (Coorporate Social Responsibility). Re-check after taking the items and before sending them to the customer. In addition, it is necessary to increase supervision of SPV Warehouse to record the entry and exit of goods in the warehouse.Keywords: Management Audit, Financial Management, Financial Management Organization Audit, Operational Policy Audit